Social Media in Support of Indonesia's One Data Interoperability Process for Implementing Data Governance Policies - Mutiarin, Dyah; Wahyuni, Herpita; Ismail, Nur Syakiran Akmal; Kumorotomo, Wahyudi (EDP Sciences, 2023)
This study aims to determine whether Twitter is a social media platform that supports the One Data Indonesia Interoperability process to implement data regulations by producing accurate, integrated and accountable data. Use of Social media in Participation, Transparency, Discussion, involvement, and Communication Strategy. This descriptive research uses NVivo 12 Plus with data sources from Twitter @diklat BIG, @datagoid, @bappenasRI, and @Jokowi via NCapture. NCapture data and use the automatically configured crosstab feature. This study shows that social media significantly drives data interoperability strategies in Indonesia. Communication indicators from Participation in previous attempts were 22.00 and 3236 referrals. The 21.00 transparency category includes clear objectives, processes and program support. They completed 20.00 of the various stages of data collection, verification, and data priority release. To socialize the implementation of One Data Indonesia and the action to accelerate the provision of the One Data Portal, tweets were used with an involvement proportion of 18.00. Communication Strategy realizes the importance of data and the existence of One Data Indonesia by using the Conversation Indicator, which has a Participation proportion of 17.00. This study is essential for analyzing social media assistance using Twitter-based activity support and providing new, up-to-date data with NVivo 12 Plus analysis. © The Authors, published by EDP Sciences.